A Case Report of Maxillary Anterior Radiolucent Lesion Associated with Impacted Teeth - Bajracharya, Barsha; Poudel, Pratibha; Bajracharya, Dipshikha; Bhattacharyya, Subrata (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
The unilocular radiolucencies, with its wide range of possible diagnosis, remain the topic of much debate and interest for clinicians. These lesions cannot be diagnosed solely based on radiographic appearance, but should be based on clinical, radiological and histopathological features. Due to high probability of misdiagnosis of this entity, a sound knowledge of various unilocular radiolucencies, adequate use of diagnostic aids and careful observation is important to provide proper diagnosis and treatment. Here, we present a case of a unilocular lesion in the right anterior maxilla with two impacted teeth.